2008
DOI: 10.1128/iai.01412-07
|View full text |Cite
|
Sign up to set email alerts
|

RespiratoryFrancisella tularensisLive Vaccine Strain Infection Induces Th17 Cells and Prostaglandin E2, Which Inhibits Generation of Gamma Interferon-Positive T Cells

Abstract: Two key routes of Francisella tularensis infection are through the skin and airway. We wished to understand how the route of inoculation influenced the primary acute adaptive immune response. We show that an intranasal inoculation of the F. tularensis live vaccine strain (LVS) with a 1,000-fold-smaller dose than an intradermal dose results in similar growth kinetics and peak bacterial burdens. In spite of similar bacterial burdens, we demonstrate a difference in the quality, magnitude, and kinetics of the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
114
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(128 citation statements)
references
References 55 publications
14
114
0
Order By: Relevance
“…In this study, we observed that CD4 + T cells produced IL-17A during LVS i.n. infection in numbers that were previously reported [∼10 4 IL-17A + CD4 + T cells/lung; Woolard et al (19)], but we further demonstrate that an additional IL-17A-producing T cell subset, DN T cells, was present in even higher numbers during the peak of LVS i.n. infection (Fig.…”
Section: Cd8supporting
confidence: 75%
See 2 more Smart Citations
“…In this study, we observed that CD4 + T cells produced IL-17A during LVS i.n. infection in numbers that were previously reported [∼10 4 IL-17A + CD4 + T cells/lung; Woolard et al (19)], but we further demonstrate that an additional IL-17A-producing T cell subset, DN T cells, was present in even higher numbers during the peak of LVS i.n. infection (Fig.…”
Section: Cd8supporting
confidence: 75%
“…Indeed, the DN T cells observed during LVS infection appear to be phenotypically most similar to an MHC class I-restricted CD4 2 CD8 2 NK1.1 2 DN T cell subset that was identified in a murine allograft rejection model (18,26). Previous studies by Woolard et al (19) following primary sublethal i.d. and i.n.…”
Section: Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the priming of Ag-specific Th17 cells and/or Ag-induced IL-17A production of isolated effector cells has been reported for many pathogens, including intra-and extracellular bacteria, fungi, viruses and parasites, but in most cases the Th17/IL-17A response does not exceed the Th1/IFN-g response (22)(23)(24)(25)(32)(33)(34). It has been suggested that intestinal Citrobacter rodentium and pulmonary Bordetella bronchiseptica infections induce a dominant Th17 cell response, but this has been observed after nonspecific restimulation with PMA/ionomycin (35) or the cellular source of IL-17A has not been defined (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies suggest that in the acute phase of infection these cytokines are predominately produced by non-T cells, innate-like gd T cells, or nonspecific ab T cells (18)(19)(20)(21). The priming of pathogen-specific Th17 has been demonstrated (22)(23)(24)(25), however, long-term maintenance and the function of Th17 cells in secondary immune responses to pathogens remain poorly understood. We demonstrate in this study that S. flexneri induces a predominant Th17 response, whereas Th1 cells that are only weakly primed and Th2 cells that are undetectable like Shigella-specific CD8 + T cells.…”
mentioning
confidence: 99%